The Effect of Education Financing on Teacher Performance at SMAT Baiturrahman - H. Soro , Suharyanto; Sariyanto, Tony; Geri, Geri (Global Education Journal, 2025)
Education financing is a crucial element in the national education system that directly or indirectly affects the quality and performance of educators. Although the education budget in Indonesia is quite large, its distribution and effectiveness are still challenges, especially in supporting teacher professionalism. This study aims to empirically determine the effect of education financing on teacher performance at SMAT Baiturrahman, especially in terms of providing facilities and infrastructure, professional training, and performance incentives. This study uses a case study approach with a survey data collection method through a Likert-scale closed questionnaire. The research sample consisted of 13 teachers taken using the total sampling technique. The data were analyzed using validity, reliability, descriptive, normality, and linear regression tests through the help of SPSS 25 software. The results of the study showed that education financing had a significant effect on teacher performance, with an R Square value of 0.513 indicating that 51.3% of the variation in teacher performance can be explained by education financing. This finding is reinforced by the results of the t-test and F-test which showed a significance of <0.05, which means that financing has a positive and significant effect. Targeted financing is a key factor in improving teacher performance. There is a positive influence on the performance of SMAT Baiturrahman teachers.